European Union–Ukraine Association Agreement: Challenges and Prospects for Cooperation - Durman, Olena; Durman, Mykola; Mazievich, Tatyana; Zhiliaieva, Oksana; Arkhypenko, Svitlana (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The purpose was to substantiate the features and determine an effective strategy for Ukraine's Eurointegration. Used a theoretical analysis of reports on the fulfillment of the terms of the European Union (EU)–Ukraine Association Agreement (AA), we identified the problems and destructive factors of the European integration for Ukraine. The graph theory helped to prioritize these problems in the context of implementing the AA's tasks. Constructed neural models and elasticity coefficients provided a quantitative assessment of the adequate performance of strategic functions within the framework of the AA for Ukraine has been carried out. Priority of conduction tasks argued the importance of implementing a strategy of moderate adaptation for Ukraine to increase the positive effect of cooperation with the EU and sustainable development of the country